2016
DOI: 10.1016/j.jece.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and lead biosorption by Curtobacterium sp. FM01, an indigenous bacterium isolated from farmland soils of northeast Iran

Abstract: the biosorbed ions. The study suggests that Curtobacterium sp. FM01 could be a promising 42 candidate with a capacity to remove Ni (II) and Pb (II) from aqueous solutions. 43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 19 publications
(6 reference statements)
4
11
0
3
Order By: Relevance
“…Masoumi et al reported that Curtobacterium sp. FM01 could be a promising candidate with a capacity to remove Ni (II) and Pb (II) from aqueous solutions [69], and their findings are similar to our results. As for dead biosorbents, FT-IR analysis indicated that the hydroxyl (-OH), alkyl (-CH 2 ), amino (-NH), nitrile (-CH), and aromatic (-C 6 H 5 ) groups were involved in Pb 2+ biosorption.…”
Section: Discussionsupporting
confidence: 89%
“…Masoumi et al reported that Curtobacterium sp. FM01 could be a promising candidate with a capacity to remove Ni (II) and Pb (II) from aqueous solutions [69], and their findings are similar to our results. As for dead biosorbents, FT-IR analysis indicated that the hydroxyl (-OH), alkyl (-CH 2 ), amino (-NH), nitrile (-CH), and aromatic (-C 6 H 5 ) groups were involved in Pb 2+ biosorption.…”
Section: Discussionsupporting
confidence: 89%
“…Thermodynamically, this implies that each biosorption process would be most spontaneous or favoured at concentration with the minimum free energy (Babarinde et al, 2008). So far, results revealed that the heavy metal ions can be removed using biosorption and these findings are in line with previous studies (Bozbaş and Boz, 2016;Bulgariu and Bulgariu, 2016;Masoumi et al, 2016;Mishra et al, 2016;Pepi et al, 2016;Ramrakhiani et al, 2016;Ronda et al, 2016;Venkatesh et al, 2016;Wei et al, 2016;Zhang et al, 2016).…”
Section: ( ) = ∆ +supporting
confidence: 86%
“…The origins of Ni (II) contamination in the environment are metal mining, glass industry, fossil fuel burning, industrial wastes, fertilizers, and vehicle emissions [21][22]. Human exposure to nickel over 0.04 mg/L in consumption water causes allergies in the form of contact dermatitis, lung fibrosis, cardiovascular and kidney diseases, and lung and nasal cancers [23][24]. In this study we tested the biosorption and phytoremediation potential of L. salicaria for nickel removal from aquatic systems.…”
mentioning
confidence: 99%